If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5y + -3(2y + -4) = 8 Reorder the terms: 5y + -3(-4 + 2y) = 8 5y + (-4 * -3 + 2y * -3) = 8 5y + (12 + -6y) = 8 Reorder the terms: 12 + 5y + -6y = 8 Combine like terms: 5y + -6y = -1y 12 + -1y = 8 Solving 12 + -1y = 8 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + -1y = 8 + -12 Combine like terms: 12 + -12 = 0 0 + -1y = 8 + -12 -1y = 8 + -12 Combine like terms: 8 + -12 = -4 -1y = -4 Divide each side by '-1'. y = 4 Simplifying y = 4
| c=5p+215 | | -19(z+2)+6(4z-4)=4(z-4)+11 | | -25=-5 | | (x-3).6+1=65 | | 2x^2-8x-5=0 | | 5y=10x+25 | | 10(5x+2)-3x=349 | | 16-3x=-4(4x+3)-4(-5-3x) | | 7x+9=19+5x | | -6x-5x=-2 | | n^2+5n-1=0 | | 2x-8=-7x+28 | | 7z=8z | | x-4=-1+8 | | 2x+4=5-6x | | 16-3x=-4(4x+3) | | 4(x-8)/5=16 | | 2y+(6+y)=12 | | x-8=6x-13 | | B^5=368 | | 2x+3=51-2x | | 2x+18-4x+12=-6 | | -2=2+(.25)v | | 4(3+c)=3(c-5) | | (x-3).6(x+1)=65 | | 9+(-2)=4+t | | 7x+1=31+4x | | 0.60x+.05(4-x)=.10(-20) | | 3(2x+6)=-6 | | 2m-9-8m=27 | | 6-2(4-8x)=2(3x-5) | | 2.5=d-(20) |